Analisis Sarana dan Prasarana Melalui Kegiatan Magang 1 di SD Swasta PAB 18 Sampali: Penelitian - Hikma Sari Harahap; Afni Ajum Pulungan; Syahril Ramadan Nasution; Afni Rahma Sagita Panjaitan; Syariah Aini Siregar; Romaito Siregar; Salim (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to describe the management of educational facilities and infrastructure as well as the implementation of learning activities at SD Swasta PAB 18 Sampali through the Teaching Practicum (Magang 1) using a qualitative descriptive approach. Data were collected through observation, interviews, and documentation, and analyzed using the interactive model of Miles and Huberman combined with SWOT analysis. The findings indicate that the school demonstrates strengths in the quality of human resources, well-organized instructional administration, and a conducive learning environment. However, limitations were identified in classroom facilities, learning technology, school playgrounds, and parking areas. Support from the foundation and community trust present opportunities for development, while competition from schools with more advanced digital facilities poses a challenge. Therefore, a gradual strategy for improving facilities and infrastructure, along with administrative digitalization, is required to support effective and sustainable learning.